Stock Market Liquidity and Firm Performance: Wall Street Rule or Wall Street Rules? - Fang, V; Noe, T; Tice, S (Oxford Finance, 2008)
This paper investigates the relation between stock liquidity and firm performance. We find that firms with liquid stocks have better firm performance as measured by the market-to-book ratio. This result holds even when we include industry or firm fixed effects, control for idiosyncratic risk, control for endogenous liquidity with instrumental variables, or use alternative measures of liquidity. To identify the causal effect of liquidity on firm performance, we study an exogenous shock to liquidity---the decimalization of stock trading---and document that the increase in liquidity around decimalization improved firm performance. We next investigate the causes of liquidity’s beneficial effect and find support for liquidity enhancing performance by increasing the information content of market prices, and strengthening the incentive effects of performance based compensation contracts. We find no evidence that liquidity enhances blockholder intervention. Finally, momentum trading, analyst coverage, investor overreaction and liquidity’s valuation effects do not appear to drive our results.